Pilot Study of Boreal Chorus Frog and Wood Frog Distribution and Aquatic Habitat Conditions in Cape Churchill, Manitoba - Boal, Clint W; Andersen, David E (2003)
Pilot study to examine the distribution and habitat associations of boreal chorus frogs (Pseudacris maculata) and wood frogs (Rana sylvatica) in the vicinity of the Nestor One Field Station, Cape Churchill, Manitoba.